BEVERNAGE, Berber. History, Memory, and State-Sponsored Violence: Time and Justice. New York/London: Routledge, 2012. 250 p. - LIMA, CAIO RODRIGO CARVALHO (Outros Tempos: Pesquisa em Foco - História, 2013)
Boa leitura!